ECONOMIC EMPOWERMENT OF SHELL CRAFTSMEN IN TELUK NIBUNG DISTRICT, TANJUNGBALAI CITY - Sopiani, Rosma; Aiyub, Aiyub; Alfiady, T.; Aisyah, Ti; Nazaruddin , Nazaruddin (Jurnal Review Pendidikan dan Pengajaran, 2025)
The economic empowerment of seashell craftsmen describes the lack of business capital to start, operate and develop a seashell craft business, lack of training and assistance for seashell craftsmen in improving their skills, lack of access to raw materials and equipment in producing seashell crafts, lack of marketing and promotion in empowerment shell craftsman. This research aims to find out the process of economic empowerment of seashell craftsmen in Teluk Nibung District, Tanjung Balai City, as well as the obstacles in the process of economic empowerment of seashell craftsmen. This research uses descriptive qualitative research methods. Data collection techniques used were observation, interviews and documentation. The data that researchers obtained was analyzed using several steps, namely data reduction, data presentation and drawing conclusions. The types of data used are primary data and secondary data. The results of this research show that the economic empowerment of seashell craftsmen carried out by the Social Service is an effort to overcome the problem of seashell crafts in Teluk Nibung District, Tanjung Balai City. The empowerment carried out by the Social Service through Dekranasda is quite good. The research results show that the economic empowerment of shell craftsmen in Teluk Nibung District can be improved through several strategies. First, increasing the skills and knowledge of craftsmen through training on more modern and efficient shell processing techniques. Second, developing a wider marketing network to expand market share. Third, providing access to business capital through collaboration with financial institutions and government programs. Apart from that, this research also found that support from the government and community is very important in supporting the sustainability of the shell craftsman business. The government's role in providing supportive facilities and policies, as well as active community participation in promoting local products, can have a positive impact on improving the economy of craftsmen. Thus, economic empowerment of shell craftsmen in Teluk Nibung District requires a holistic approach involving various parties, including the government, craftsmen and the community, to achieve better and more sustainable economic prosperity.